Who are our farming families? Utilising the Administrative Data | Agricultural Research Collection (AD|ARC) for Wales. - Hargreaves, Claire; Caskie, Paul; Morrison-Rees, Sian (International Journal of Population Data Science, 2025)
Objectives Policies designed to support the sustainability of farming are multiple, although developed with little knowledge about the intricacies of farming households. To inform policy and support strategies, more information is needed about the families involved, including their characteristics, economic circumstances and resilience. Methods De-identified data on farm households from the Administrative Data | Agricultural Research Collection (AD|ARC) is utilised within the SAIL Databank. AD|ARC contains characteristics of the farmer, farm household (all children and adults living in the household) and farm business, for all members of households in Wales living at an address for which a farm business received a subsidy payment in 2010. The population comprises approximately 18,000 farm businesses and linked farm households in Wales, and a comparison group of non-farming rural households. The demographic, household and self-reported health characteristics of individuals in the two groups was compared. Results Descriptive and bivariate statistics will be used to describe farm households in Wales in terms of the farmer (e.g. farmer’s age, gender, ethnicity, education), farm household (e.g. household members age, gender, ethnicity, education, employment, income, household composition, total income, deprivation), and farm business (e.g. number of farmers and non-farmers, employed workers, agricultural training, farm activity, area of land, total subsidy payment) characteristics. The profile of farming households in Wales will then be compared with those of the rural control group held in the AD|ARC data set. Through bivariate and multivariate statistics and generalised linear models, the analysis will highlight characteristics specific to the farming community or reflective of rural communities in general. Conclusion This research investigates the characteristics, economic circumstances and resilience of farming households in Wales. The findings have important implications for agricultural policy, and for health and other services, and will aid policy makers and farming stakeholders in anticipating the diverse impacts of policies across the farming community.